Pemberdayaan Desa Batu Ampar Melalui Pemasaran Digital Madu Hutan Mangrove: Studi Kasus PKM-KI Mahasiswa Pascasarjana Ekonomi Syariah IAIN Pontianak - Noviansyah; Syahbudi; Gunawan; Ismail Ruslan; Ridho Arnanda (Universitas Islam Tribakti Lirboyo Kediri, 2024)
This study examines the community's reliance on mangrove forests, particularly through the establishment of charcoal kiln businesses as a primary livelihood in Batu Ampar Village, following the decline of sawmill operations. The production of charcoal requires large quantities of mangrove wood, leading to significant environmental impacts, including the reduction of mangrove forests, increased carbon emissions, and deteriorating public health. In response to these challenges, social movements among mangrove honey farming groups have emerged, focusing on ecological revitalization efforts. This research aims to explore the role of social movement strengthening through mentoring by PKM-KI students from the Sharia Economics Master's program, specifically in the development of digital platform-based marketing strategies for mangrove honey businesses. Using a qualitative descriptive approach, the study analyzes field data to evaluate the effectiveness of digital marketing in promoting mangrove honey as an alternative livelihood. The results highlight the potential of digital platforms in expanding the market for local mangrove honey products, offering a sustainable livelihood for the community while supporting environmental conservation.